Astronomical control on upper ordovician – lower silurian organic matter enrichment in South China - Yong, Jinjie; Hu, Shaoyong; He, Jie; Liu, Zhicheng; Zheng, Mengtian; Luo, Peng; Liu, Xin; Dong, Wei (Frontiers in Earth Science, 2025)
Astronomical forcing governed Late Ordovician–Early Silurian climate dynamics, yet high-resolution Astronomical Time Scales (ATS) and organic enrichment mechanisms during the end-Ordovician extinction remain poorly constrained. In this study, we integrated gamma ray (GR), δ13Corg, and chemical index of alteration (CIA) data from the Wufeng–Longmaxi formations (Weimohani section, South China) to establish a floating ATS tuned to 405-kyr eccentricity cycles, anchored to a Hirnantian U–Pb age (444.2 ± 1.6 Ma). This ATS constrains key stage durations (Hirnantian: 1.31 Myr; 432.19–444.01 Ma span) and confirms orbital control on eustasy: 1.2-Myr obliquity paced third-order icehouse-greenhouse transitions, while 405-kyr eccentricity drove fourth-order sea-level fluctuations. The CIA records demonstrate that obliquity-modulated thermohaline circulation enhanced nutrient flux to the Yangtze Shelf, with peak organic enrichment occurring during transitional climates (δ13Corg minima plus CIA maxima) rather than glacial extremes. These findings reveal a eustatic (orbital) dominance over tectonic controls and resolve the synergistic productivity-preservation balance governing organic matter accumulation.